Subjective assessment of health status and preparation for self-care among patients suffering from chronic kidney disease and diabetes - Marzec, Alicja; Walasek, Lech; Andruszkiewicz, Andruszkiewicz (Nursing in the 21st Century, 2012)
SUBJECTIVE ASSESSMENT OF HEALTH STATUS AND PREPARATION FOR SELF-CARE AMONG PATIENTS SUFFERING FROM CHRONIC KIDNEY DISEASE AND DIABETES Introduction. In the chronic kidney disease and diabetic nephropathy, requiring treatment haemodialysis, it is important to prepare the patient for living with the disease by increasing the capacity for self-care and complete knowledge of the disease. This determines the autonomy of the patient in functioning. Aim. The aim of the work was to determine whether there are differences in the in self-evaluation of health, in the assessment of preparation for self caring among patients with chronic kidney disease and diabetes. Material. The study comprised 236 persons in 4 groups: 1) patientswith chronic kidney disease in the CKD efficiency stage, 2) patients with chronic kidney disease at stage V, treated with haemodialysis CKD-HD, 3) patients with diabetes C and 4) patients with diabetes and diabetic nephropathy, treated with haemodialysis, group CKD-HD. Method. The questionnaire survey (developed by authors) was used to collect research data. Results. Differences in self-assessment of health status between groups are significant. None of the patients treated with HD considered their health as good. Those with CKD had the problems with self-assessment of health (as much as 48% of patients considered their condition as good), and patients with diabetes (up 19.23% were not able to make self-assessment). Conclusions. The respondents have difficulty in self-assessment of health status. Patients regarded themselves to be well-prepared for self-care. These are overestimated ratings, so it is appropriate to carry on health education to these patients on regular basis.